PROBLEMS OF MONUMENTAL SCULPTURE SYNTHESIS IN ENSEMBLES OF THE CITY OF MAKHACHKALA - T. S. Gamidov (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The main objective was to study the problem of synthesising monumental sculpture in architectural ensembles of the city of Makhachkala. The term “problems of synthesis” includes a number of key rules and patterns, from the correct solution of which depends the harmonious inclusion of monuments in the environment.Methods. The study of monumental art installations is based on the methodological and theoretical studies of Soviet art historians and architectural researchers, based on a wide range of requirements for the installation of monuments in an urban environment. The research methods also include the spiritual and aesthetic, formal-stylistic and ideological-content aspects of the analysis of works of monumental art.Results. The most famous sculptural monuments of the city of Makhachkala were analysed, the positioning of which required the authors to solve art-aesthetic and spatial-compositional problems intelligently, ensuring positive perception of the monuments in connection with the architectural layout of the city. Various historical situations of specific locations of Makhachkala were explored (road forks, island sections of ring roads, parks, squares, alleys, etc.), which create favourable or unfavourable conditions for the installation of sculptural monuments. The main provisions given in this article can be used as a criterion for evaluating and analysing works of monumental art as well as to provide methodical guidelines in planning development for both the construction of new and the reconstruction of old monuments of the capital.Conclusion. The urban development of Makhachkala, involving high density residential areas and a profusion of monuments in the ring roads and squares, requires a special, creatively sensitive approach to problems of synthesis of architecture and plastic arts, on which both the harmonious appearance of urban ensembles and a comfortable living environment depends. The choice of the monument type and its ideological and semantic canvas for a specific locality, the solution of composition-spatial problems, the establishment of scale and limits of near and far points of view, the direction of lighting, colour, texture, individually provided for each individual monument, comprise the main imperatives underpinning the creative approach of Dagestan sculptors and architects working on the improvement of our capital city.